Development of Drama and Performance Textbooks to Improve the Creative Thinking Abilities of Prospective Indonesian Language Teacher Students - Soleh, Dwi Rohman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research aims to develop drama and performance textbooks to improve the creative thinking abilities of prospective Indonesian language teacher students. The research method used in this research is the DR (Development Research) ADDIE (Analysis, Development, Implementation, and Evaluation) method. This technique is used to analyze qualitative data obtained from interviews and questionnaires conducted with students, instructors, and experts. In addition to qualitative data, quantitative data is collected through pretest and posttest assessments. These tests measure students' creative thinking abilities before and after using the learning package. The results of this research are a learning package refers to a comprehensive set of educational materials and resources developed to achieve specific learning outcomes. In this study, the learning package consists of drama and performance textbooks created for prospective Indonesian Language teacher students. The textbooks are designed to facilitate learning by providing structured content, exercises, examples, and activities aimed at stimulating creative thinking and improving teaching abilities. The learning package is not limited to textbooks alone but may also include supplementary materials, such as online resources, instructional videos, and activities for classroom engagement. Drama and performance textbooks designed to improve the creative thinking skills of prospective Indonesian language teacher students show valid results, but the validator suggests that the textbooks should be improved for use by students. After being revised according to the validator's suggestions, the textbook can be tested to determine student reactions.